4CPS-355 Evaluation of patients consulting the emergency department for bradycardia related to medication. (14th March 2021) - Gras Martín, L; Ruiz, J; Juanes, A; Puig, M; Blázquez, M; Mangues, MA
Abstract : Background and importance: Drug related problems are one of the main causes requiring assistance by the emergency units (EU), with bradycardia being one of the most frequent presentations. However, information related to the frequency of revisits to the EU depending on treatment changes at discharge is scarce. Aim and objectives: To describe the treatments that cause visits to the EU for bradycardia and to identify the interventions carried out and the revisits to the EU 30 days after discharge. Material and methods: A retrospective observational study was carried out in patients who attended the EU of a tertiary hospital for drug related bradycardia from September 2018 to March 2020. Results: 41 patients with a mean age of 81.2 years (range 55–96) undergoing treatment with negative inotropic drugs were included. All patients treated with more than one drug were taking a beta-blocker. Four (30.8%) patients with dual therapy were taking flecainide concomitantly, four (30.8%) digoxin, three (23.1%) amiodarone and two (15.4%) diltiazem. 7.3% of the patients received the drug as a single dose, 9.8% started treatment the week before, 2.4% the month before and 12.2% in the last 3 months. Ten (24.4%) presented altered creatinine clearance and 17 (41.5%) had chronic renal failure. In 14 (34.1%) patients one drug was suspended, in five (12.2%) two were suspended, in five (12.2%) the drug was changed, in seven (17.1%) the dose was decreased and in 10 (24.4%) treatment was not changed. Pacemakers were placed in 11 (26.8%) patients. 12 (29.3%) patients revisited the EU 30 days after discharge and 6 (50%) were admitted. Four (9.8%) patients consulted for an episode related to the previous one: 1 due to vasovagal syndrome after implantation of pacemaker without changes in treatment, 1 due to bradycardia after suspending bisoprolol but continuing with amiodarone and 2 due to AF after suspending any drug. Conclusion and relevance: Beta-blocker drugs were the main cause of pharmacological bradycardia, being used in most of the episodes as monotherapy and to treat atrial fibrillation. This group of patients presented with a high frequency of revisits at 30 days even after previous intervention. This is a potential group that could benefit from pharmacist follow-up after discharge. References and/or acknowledgements: Conflict of interest: No conflict of interest